Efficient Data Mining Technique in Higher Education System: Analysis with Reference to Madhya Pradesh: Exploring Data Mining Techniques in Higher Education System: A Case Study in Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data mining is a procedure which finds helpful examples from expansive measure of data. The paper examines few of the data mining methods, calculations and a portion of the associations which have adjusted data mining innovation to enhance their organizations and discovered brilliant outcomes. The data mining in light of Neural Network and Genetic Algorithm is examined in detail and the key innovation and approaches to accomplish the data mining on Neural Network and Genetic Algorithm are likewise reviewed.